Removal of ibuprofen and amoxicillin in domestic wastewater using activated carbon soaps and moringa seed powder at the laboratory level (SCIÉNDO INGENIUM, 2024)
This research was done to determine the effect of using soaps with activated carbon and moringa seed powder on the concentration of ibuprofen and amoxicillin in domestic wastewater. The soaps were prepared with transparent commercial glycerin, adding the adsorbents at a rate of 0.1 g/g of soap. The residual water was prepared in the laboratory and characterized, then ibuprofen and amoxicillin were added at a concentration of 3 mg/L each. In the experiments, the soaps were added individually and combined to 1 liter of residual water, in three weight percentages: 5%, 15% and 25%. The combined application of soap with activated charcoal and 25% moringa seed powder was the best treatment with removal of 81.33% and 80% of ibuprofen and amoxicillin, respectively. This treatment was applied to actual domestic wastewater from the wastewater outlet to the Huallaga River in Tingo María-Huánuco-Perú, which was characterized and 72.3% and 69.7% of ibuprofen and amoxicillin were removed, respectively. Through a Tukey test, it was verified that there is a significant difference with a confidence interval of 95%, between the treatments applied in a real residual water and an artificial one.
Keywords: Activated carbon; Moringa seeds; Ibuprofen; Amoxicillin; Domestic wastewater